Pengembangam Modul Ajar Fisika Berbasis Literasi Sains untuk Meningkatkan Kemampuan Berpikir Analisis Peserta Didik - Nurul Amalia Aris; Muhammad Arsyad; Helmi Abdullah (Postgraduate, University of Mataram, 2024)
This research is a type of R&D research using a 4D model. The 4D stages include define, design, develop, and disseminate. This research and development aims to analyze the validity of the content of the developed science literacy-based physics teaching module design, analyze practitioners' assessments of science literacy-based physics teaching modules, and analyze the effectiveness of using science literacy-based physics teaching modules to improve students' analytical thinking skills. Based on the results of the analysis, it can be concluded that the science literacy-based physics teaching module developed based on expert assessment using the Aiken V index analysis is declared valid and feasible to use with a little revision, the science literacy-based physics teaching module in terms of practitioner (teacher) responses for all aspects obtained an average score percentage of 86% which is on very good criteria, and the effectiveness of using science literacy-based physics teaching modules is obtained from the results of tests of students' analytical thinking skills as many as 77% of students are on an N-gain score of 56% or with effective criteria where this means there is an increase in students' analytical thinking skills in physics learning.